Sex, Age, Anatomic Location, and Extent of Resection Influence Outcomes in Children With High-grade Glioma. Issue 3 (September 2015) - McCrea, Heather J.; Bander, Evan D.; Venn, Rachael A.; Reiner, Anne S.; Iorgulescu, J. Bryan; Puchi, Luis A.; Schaefer, Peter M.; Cederquist, Gustav; Greenfield, Jeffrey P.
Abstract : BACKGROUND: Survival duration and prognostic factors in adult high-grade glioma have been comprehensively analyzed, but less is known about factors contributing to overall survival (OS) and progression-free survival (PFS) in pediatric patients. OBJECTIVE: To identify these factors in the pediatric population. METHODS: We retrospectively reviewed institutional databases evaluating all patients ⩽21 years with high-grade glioma treated between 1988 and 2010. Kaplan-Meier curves and log-rank statistics were used to compare groups univariately. Multivariate analyses were completed using Cox proportional hazards regression models. RESULTS: Ninety-seven patients were identified with a median age of 11 years. Median OS was 1.7 years, and median PFS was 272 days. Location was significant for OS ( P < .001). Patients with gross total resection (GTR) had a median OS of 3.4 years vs 1.6 years for subtotal resection and 1.3 years for biopsy patients ( P < .001). Female patients had improved OS ( P = .01). Female patients with GTR had a mean OS of 8.1 years vs 2.4 years for male patients with GTR and 1.4 years for all other female patients and male patients ( P = .001). PFS favored patients ⩽3 and ≥13 years and females ( P = .003 and .001). CONCLUSION: OS was significantly correlated with the location of the tumor and the extent of resection. GTR significantly improved overall survival for both glioblastoma multiforme and anaplastic astrocytoma patients, and female patients showed a much larger survival benefit from GTR than male patients. ABBREVIATIONS: AA, anaplastic astrocytoma GBM, glioblastoma multiforme GTR, gross total resection HGG, high-grade glioma OS, overall survival PFS, progression-free survival STR, subtotal resection WHO, World Health Organization Abstract : Supplemental Digital Content is Available in the Text.